Determination of the seroprevalence of bovine leukemia virus in a dairy farm of Lima, Peru - Sandoval M., Rocío (2015)
The aim of this study was to determine the seroprevalence of the bovine leukemia virus in a dairy farm of a public university of Lima, Peru through the circulating antibodies against the virus. The disease is prevalent in the farm as in many other dairy farms in the area. The results showed a prevalence of 92.7% (51/55), where 100, 97, and 60% of animals older than 5 years old, from 2 to 5 years old, and less than 2 years old were seropositive respectively. It is recognized the importance of initiating a control and eradication programme that can be used as a model for other commercial dairy farms in the Lima region.